Applied asset and risk management : a guide to modern portfolio management and behavior-driven markets - Schulmerich, Marcus; Leporcher, Yves-Michel; Eu, Ching-Hwa (Management for Professionals,, 2015)
This book is a guide to asset and risk management from a practical point of view. It is centered around two questions triggered by the global events on the stock markets since the middle of the last decade: - Why do crashes happen when in theory they should not? - How do investors deal with such crises in terms of their risk measurement and management and, as a consequence, what are the implications for the chosen investment strategies? The book presents and discusses two different approaches to finance and investing, i.e., modern portfolio theory and behavioral finance, and provides an overview of stock market anomalies and historical crashes. It is intended to serve as a comprehensive introduction to asset and risk management for bachelor's and master's students in this field as well as for young professionals in the asset management industry. A key part of this book are the exercises to further demonstrate the concepts presented with examples and a step-by-step business case. An Excel file with the calculations and solutions for all 17 examples as well as all business case calculations can be downloaded at extras.springer.com. In this book modern portfolio theory meets behavioral finance, resulting in new insights in state-of-the-art investing. Not only practitioners but also students and academics benefit from the combination of professional capital market experience and academic wisdom as well as the many exercises the book uses to bring the concepts alive. Especially the chapter covering recent investment trends broken down by investor type and region should prove very useful for investment professionals in the asset management industry in Europe. Highly recommended! Dr. Christian Schmitt, Managing Director, risklab GmbH - AllianzGI Global Solutions, Munich, Germany The book provides a comprehensive introduction to modern asset management and behavioral finance. Using interesting business cases and a hands-on approach with Excel exercises, the authors lead the reader to tackle the main challenges in modern asset and risk management, with a practical focus on behavioral finance. For bachelor and master students who want to get a structured and detailed introduction to asset management, risk management and behavioral finance I can highly recommend this book! Prof. Sandra Paterlini, Ph.D., Chair of Financial Econometrics and Asset Management, EBS - Business School, Wiesbaden, Germany.